Pemikiran Muhammad Abduh tentang Pembaharuan Pendidikan - Rizki A. Ramadhani; Nurhayati Masani; Mustamin Giling (Al-Kindi, 2026)
Muhammad Abduh was one of Egypt's most influential Islamic reformers. He was not only a great scholar, but also a renowned writer, a successful educator, and a reformer of modern Egypt. His contribution to Islamic thought. One of Abduh's most important contributions was his contribution to the development of a new educational system in Egypt and other Islamic countries. He realized that education was the key to freeing Muslims from the shackles of stagnation and backwardness. Therefore, he encouraged the establishment of educational institutions that taught not only religious knowledge, but also general knowledge and practical skills. In this study using library methods, the formulation of the problem in this study is 1) How is the Life History of Muhammad Abduh? 2) How are Muhammad Abduh's Ideas Related to Anti Staticism, Rationalism, and Educational Reform? The results of this study are that Abduh succeeded in awakening the spirit of reform in education in the Islamic world. He emphasized the importance of education based on reason and experience, and encouraged Muslims not only to be trapped in dogma, but also to develop critical thinking.